Perlite concrete. 2. Dimensional changes due to change of water content - Blakey, F. A. (Frank A.) (Report C (CSIRO. Division of Building Research) ;, 1958)
The effects are studied of four different curing treatments on the shrinkage, moisture movement and absorption of perlite concretes of four different mix proportions, The susceptibility to cracking is also examined. The results follow the expected pattern in so far as movements and absorption increase with increasing cement content. At constant consistency air entrainment did not affect the shrinkage significantly but did reduce the tendency to crack.